PSMA PET/CT vs. MRI-DWI in Diagnosis of Early Metastasis of Prostate Cancer - Nizar, Hanna; Konstantin, Kenigsberg; Alex, Pavlov; Natalia, Goldberg (Archives of Clinical and Medical Case Reports, 2024)
Accurate staging is crucial in the management of prostate cancer. Advanced radiological technologies like PSMA PET-CT and whole-body MRI have proven to be more effective in detecting metastasis compared to traditional methods such as 99mTc-bone scintigraphy [1]. The effectiveness and diagnostic accuracy of these new technologies are still being evaluated. Early detection of metastasis can significantly impact the treatment plan for patients. In the early stages, options like systematic therapy with androgen receptor targeted agents or metastatic ablative strategies can be considered. Research is ongoing to determine the ideal medical imaging test with the highest diagnostic accuracy for prostate cancer staging.